Surge in Caesarean Section Rates across the Indian Subcontinent: A Systematic Review - Farah Niazi; Kalsang Choedon; Mehwish Iqbal; Karuna Nidhi Kaur; Shazina Saeed; Mohd Shannawaz (Preventive Medicine: Research & Reviews)
The increase in caesarean sections (CS) globally and specifically in the Indian subcontinent is a subject of interest in maternal healthcare, considering both the benefits and risks associated with the procedure. This study aims to assess the rate of CS in the Indian subcontinent, analysing data from 10 articles encompassing 702,930 pregnant women aged 15–49 years. The findings show varying CS rates, with Bangladesh at 13.80%, India at 13.74% and Nepal at 4.60%. Factors, such as maternal age, education, place of birth and wealth quintile, were linked to these rates. The study also notes post-partum infection as a common complication associated with CS. The research focuses on three aspects: The prevalence and determinants of CS, the outcomes for mothers and neonates and the impact of CS on healthcare resources. It underscores the need for balanced antenatal counselling and informed decision-making to optimise the use of CS, considering both its necessity in certain cases and the associated healthcare implications.